Disruption of the Photoreceptor Inner Segment–Outer Segment Junction in a 6-Year-Old Girl with Joubert Syndrome. (2nd January 2017) - Baba, Shimpei; Takeshita, Eri; Yamazaki, Hiroko; Tarashima, Mikako; Sasaki, Masayuki
ABSTRACT: Joubert syndrome (JS) is a spectrum of genetic disorders characterised by cerebellar and brainstem malformation called "molar tooth sign", resulting in hypotonia, developmental delay, and intellectual disability. Here we describe a young female JS patient with "salt-and-pepper" fundus and inner segment–outer segment junction (IS/OS line) discontinuity, with a lack of external limiting membrane. Ocular coherence tomography (OCT) detected blurred external retinal layers in the macula centre. Although JS patients often have retinal degeneration with varying severity, few investigators have utilised OCT in their investigations. Our findings will help clarify the precise mechanisms of retinal involvement in JS.